Assessing Privacy Risks in Metaverse Environments: A Comparative Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The metaverse is a hybrid cyberspace and living room that brings the idea of digitalizing and virtualizing the physical world to fruition. In an effort to map the actual world and beyond it incorporates a myriad of current technology. The future of metaverse is bright, and it will likely find numerous uses in many different contexts. As a number of associated technologies reach maturity, the Metaverse will be able to continue operating. Therefore, it's safe to say that creating the Metaverse might raise more serious security issues significant and intricate. We go over a few technologies that are connected to the Metaverse and discuss some possible concerns with privacy and security in the Metaverse. Based on these technologies, we provide present-day possibilities for enhancing the Metaverse's security and privacy. Furthermore, we also bring up certain open-ended questions about the prospective Metaverse. All things considered, this study examines the privacy and security concerns brought up by important technologies used in Metaverse applications in great detail. In particular, we are hoping that the survey's questions on Metaverse security and privacy may point researchers in the direction of promising new avenues of study and future paths for the Metaverse's evolution.